2009
DOI: 10.1063/1.3112740
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of the near-field dynamics of annular gas-liquid two-phase jets

Abstract: Direct numerical simulation has been used to examine the near-field dynamics of annular gas-liquid two-phase jets. Based on an Eulerian approach with mixed fluid treatment, combined with an adapted volume of fluid method and a continuum surface force model, a mathematical formulation for the flow system is presented. The swirl introduced at the jet nozzle exit is based on analytical inflow conditions. Highly accurate numerical methods have been utilized for the solution of the compressible, unsteady, Navier-St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…After that, Xiao et al [34] resolved the jet flow approach without the flow inside the nozzle. On the other hand, the evaluation of the in-nozzle swirl effect on the flow field of annular gas-liquid jets was studied by Siamas et al [35] using detailed VOF simulations. They reported that central recirculation region was developed as a result of the swirling motion.…”
Section: Introductionmentioning
confidence: 99%
“…After that, Xiao et al [34] resolved the jet flow approach without the flow inside the nozzle. On the other hand, the evaluation of the in-nozzle swirl effect on the flow field of annular gas-liquid jets was studied by Siamas et al [35] using detailed VOF simulations. They reported that central recirculation region was developed as a result of the swirling motion.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al [34] simulated the jet flow approach without the flow inside the nozzle. On the other hand, the evaluation of the in-nozzle swirl effect on the flow field of annular gas-liquid jets was studied by Siamas et al [35] using detailed VOF simulations. They reported that central recirculation region was developed as a result of the swirling motion.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Soteriou 19 numerically investigated the atomization characteristics in a practical swirling flow and qualitatively demonstrated the validity and feasibility of the coupled LS and VOF approach through experimental results. As demonstrated by Siamas et al., 20 many of the existing studies on annular swirling liquid jets focused on experimental visualizations and simplified physical models, which were insufficient to reveal the details of complex liquid breakup and atomization in a two-phase environment.…”
Section: Introductionmentioning
confidence: 99%